Translating Presuppositions. Issue 2 (August 2019) - Kroeger, Paul R.
Expressing source language (SL) presuppositions as presuppositions in the receptor language (RL) is sometimes impossible, due to linguistic differences between the languages. In other cases it can cause problems of comprehension or naturalness for RL readers, especially when the "presupposition" constitutes new information to the reader. The most common solution to such problems is to express the presupposed content as a separate assertion. This strategy preserves the propositional content of the original but distorts the information packaging. Another strategy that may be useful in such cases is to render the problematic SL presupposition as aconventional implicature, preserving the "backgrounded" status of the presupposed information without triggering an inference that this information is already known to the addressee.